APPLICATION OF THE PRINCIPLES OF CORPORATE GOVERNANCE IN AGRICULTURE COOPERATIVES - Maričić, Goran; Škorić, Sanja; Radenković, Danijela (Economics of Agriculture, 2018)
The principles of corporate governance in the global economies and in the process of globalization are recognized and stated as extremely important, first in the successful business of companies and gaining competitiveness on the market, and then in the successful resolution of possible conflicts and conflicts of different interest groups within the companies themselves. However, can corporate governance principles be applied in agricultural cooperatives, which now, more than ever, require a good organization, the structure of the rules on which they will be more organized on the market and represent the interests of their cooperatives? By analyzing the cooperative sector, its been attempted to integrate the principles of corporate governance, with the functioning of agricultural cooperatives, their basic values, organization, traditional organization, etc. in a way that they do not stand one against the other, but one in the function of the other, as a mutual complement.